Association between Changes in Preoperative Serum Creatinine and Acute Kidney Injury after Cardiac Surgery: A Retrospective Cohort Study - Bo Jiang; Yi Hao; Haiping Yang; Meiping Wang; Ran Lou; Yibing Weng; Genshen Zhen; Li Jiang (Karger Publishers, 2024)
Introduction: Limited information exists regarding the impact of preoperative serum creatinine changes on cardiac surgery-associated acute kidney injury (CSA-AKI). This study aimed to investigate the development of AKI in patients with a baseline estimated glomerular filtration rate of ≥60 mL/min/1.73 m2 who present with an elevation in preoperative serum creatinine. Methods: This retrospective cohort study assessed patients who underwent open-heart surgery. Preoperative serum creatinine change was calculated as the ratio of the maximum preoperative serum creatinine value to the baseline creatinine (MCR). Patients were categorized into three groups based on MCR: non-elevation (≤1.0), mild elevation (1.0 to 1.5), and pronounced elevation (≥1.5). Multivariable logistic regression was used to estimate the risk of AKI, severe AKI, and non-recovery from AKI. Results: There were significant increases in the odds of AKI (adjusted odds ratio [OR], 1.42; 95% confidence interval [CI], 1.29-1.57; per 0.1 increase in MCR), severe AKI (adjusted OR, 1.28; 95% CI, 1.15-1.41), and AKI non-recovery (adjusted OR, 1.29; 95% CI, 1.16-1.43). Pronounced elevation in preoperative serum creatinine was associated with a higher risk of AKI (adjusted OR, 15.45; 95% CI, 6.63-36.00), severe AKI (adjusted OR, 3.62; 95% CI, 1.20-10.87), and AKI non-recovery (adjusted OR, 4.74; 95% CI, 1.63-13.89) than non-elevation. Mild elevation in preoperative serum creatinine was also significantly associated with AKI (adjusted OR, 3.76; 95% CI, 1.92-7.37). Conclusions: Elevation in preoperative serum creatinine from baseline was associated with an increased risk of AKI; even mild elevation significantly increased the risk of AKI.